Pengembangan E-book KEDASA untuk Meningkatkan Pemahaman Siswa pada Pembelajaran IPS di Sekolah Dasar - Delia Novarini Cahyadi; Diah Gusrayani; Rana Gustian Nugraha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research focuses on the development of a learning product called KEDASA e-book, which aims to improve students' understanding of social studies learning in grade IV SD. This research applies mixed methods, which is a combination of Research and Development (R&D) and pre-experiment methods, by applying the ADDIE development model. To test the effectiveness of the e-book, a One-Group Pretest-Posttest research design was used. Data collection methods include interviews, questionnaires, and tests, while data analysis includes descriptive quantitative analysis and inferential statistics. The results of the KEDASA e-book media validation are very promising, with percentages from material experts (90%), language experts (98.33%), and media experts (93.78%). Practical trials also showed results with the percentage results of individual trials (95.79%), small group trials (93.16%), and large group trials (95.72%) with very feasible categories that can be used without improvement. The main findings of this study show a significant increase in students' understanding of social studies learning after using the KEDASA e-book. These results prove that the KEDASA e-book is a learning media that is quite effective and can be used in elementary schools to improve students' understanding of social studies learning. Thus, this study concludes that KEDASA e-book media is proven to be a learning media that can enhance students' understanding of social studies learning and offers an interesting new approach to teaching this subject in elementary schools.